Data element embedding and firm performance: The influence of ESG investment - Jianqiang, Gu; Rong, Lu; Juan, Xu (Frontiers in Environmental Science, 2022)
ESG is a brand-new concept about how environmental, social and corporate governance supports sustainable development in enterprises. However, little research is done on how to reshape the internal mechanism by which data element embedding drives enterprise performance based on the brand-new sustainable concept. From the perspective of contingency theory and organizational agility, a conceptual model including ESG investment, data element embedding, organizational agility and environmental uncertainty is constructed to study the internal mechanism by which data element embedding affects enterprise performance. The model is empirically researched through the data obtained from the survey of 287 manufacturing enterprises in China. The results show that, ESG investment and external data element embedding impose no direct impact on enterprise performance, but create an indirect impact through organizational agility; environmental uncertainty negatively moderates the effect of ESG investment on organizational agility. Through the hierarchical analysis of ESG investment and data elements embedded in enterprise performance, the value creation mechanism of data elements is revealed, which enriches and expands the theory of data elements and organizational agility, and provides enlightenment for ESG investment to drive the value creation of data elements.